Fetal Doppler to predict cesarean delivery for non-reassuring fetal status in the severe small-for-gestational-age fetuses of late preterm and term - Ji Hye Jo; Yong Hee Choi; Jeong Ha Wie; Hyun Sun Ko; In Yang Park; Jong Chul Shin (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveTo evaluate the significance of fetal Doppler parameters in predicting adverse neonatal outcomes and the risk of cesarean delivery due to non-reassuring fetal status, in severe small for gestational age (SGA) fetuses of late preterm and term gestation.MethodsFetal brain and umbilical artery (UmA) Doppler parameters of cerebroplacental ratio (CPR) and UmA pulsatility index (PI) were evaluated in a cohort of 184 SGA fetuses between 34 and 41 weeks gestational age, who were less than the 5th percentile. The risks of neonatal morbidities and cesarean delivery due to non-reassuring fetal status were analyzed.ResultsUnivariate analysis revealed that abnormal CPR was significantly associated with cesarean delivery due to non-reassuring fetal status (P=0.018), but not with neonatal morbidities. However, abnormal CPR did not increase the risk of cesarean delivery due to non-reassuring fetal status in multivariate logistic regression analysis. Abnormal CPR with abnormal PI of UmA was associated with low Apgar score at 1 minute (P=0.048), mechanical ventilation (P=0.013) and cesarean delivery due to non-reassuring fetal status (P<0.001), in univariate analysis. It increased risk of cesarean delivery for non-reassuring fetal status (adjusted odds ratio, 7.0; 95% confidence interval, 1.2-41.3; P=0.033), but did not increase risk of low Apgar score or mechanical ventilation in multivariate logistic regression analysis.ConclusionAbnormal CPR with abnormal PI of UmA increases the risk of cesarean delivery for non-reassuring fetal status, in severe SGA fetuses of late preterm and term. Monitoring of CPR and PI of UmA can help guide management including maternal hospitalization and fetal monitoring.